Polyolefin resin foam and molded products made from it

JP7644756B2Active Publication Date: 2025-03-12LOTTE CHEM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022526401
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-29
Filing Date
2020-11-27
Publication Date
2025-03-12
Estimated Expiration
2040-11-27

AI Technical Summary

Benefits of technology

【0022】 本発明の一実施態様に係るポリオレフィン系樹脂発泡体は、106Ohm/sq以下の優れた表面抵抗を示す成形品を提供することができ、これによって帯電防止性能が安定的に具現され得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644756000001
    Figure 0007644756000001
Patent Text Reader

Abstract

The present invention relates to a polyolefin resin foam and a molded article made therefrom, which comprises a polyolefin resin and a conductive filler including carbon nanotubes and carbon black, wherein the weight ratio of the carbon nanotubes to the carbon black is about 1:1.5 to about 1:5. The polyolefin resin foam according to the present invention contains carbon nanotubes and carbon black in an appropriate ratio, which allows the production of molded articles that exhibit good adhesion during molding and low surface resistance and surface resistance deviation.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyolefin resin foam and a molded article produced therefrom, and more particularly, to a polyolefin resin foam that contains carbon nanotubes and carbon black in an appropriate ratio, and thus can be used to produce a molded article having good adhesion and excellent surface resistance performance, and a molded article produced therefrom. [Background technology]

[0002] Generally, polystyrene resins, polyurethane resins, polyolefin resins, etc. are used for foamed products made from synthetic resins. Among these, polyolefin resins are environmentally friendly and recyclable, so their use is on the rise, and their foaming is being continuously developed. Furthermore, molded products made from the polyolefin resin foams exhibit excellent properties such as chemical resistance, heat resistance, and compressive strength, so they are used in a wide range of applications such as packaging materials, building materials, and automotive part materials.

[0003] However, since most polyolefin resins are non-polar polymeric materials, they have the disadvantage that the molded product itself easily becomes charged or charges the other material due to friction between molded products after manufacture is completed, friction between the molded product and other materials, or external electrical forces around the molded product, generating static electricity. Since such charging phenomenon can cause damage and contamination to products, there is a need to impart electrical conductivity and antistatic properties.

[0004] Patent Document 1 (JP Patent Publication 7-304895A) discloses polypropylene resin foam particles obtained by foaming resin particles containing a polypropylene resin and a nonionic surfactant having antistatic properties. However, the foam produced from the resin foam particles according to Patent Document 1 has a low viscosity of 10 ... 9 It exhibited a high surface resistance of over Ohm / sq, which caused problems of humidity dependency and deterioration over time.

[0005] Therefore, 106 As a method for providing a polyolefin resin composition capable of producing a foam having a low surface resistance of ohm / sq or less, a method including a conductive filler such as carbon black, graphite, carbon fiber, metal powder, metal-coated inorganic powder, or metal fiber has been considered.

[0006] For example, Patent Document 2 (JP Patent Publication 2005-256007A) discloses expandable resin particles obtained by impregnating polypropylene resin particles containing 10% by weight or more of conductive carbon and 0.01% by weight to 5% by weight of a water-soluble inorganic substance with a blowing agent and expanding the particles. 6 In order to obtain a foam with a high ohm / sq, a high content of conductive carbon is necessary. However, a high content of conductive carbon may cause problems of dust generation and reduced workability.

[0007] Meanwhile, Patent Document 3 (Korean Patent Publication No. 2019-0071184) discloses a conductive foam bead comprising a resin composition including a polyolefin resin; a carbon nanotube aggregate consisting of a plurality of carbon nanotubes having an average outer diameter of 8 nm to 50 nm and an average inner diameter of 40% or more of the average outer diameter; and a foaming agent, the conductive foam bead including a plurality of cells having an average diameter of 10 μm to 200 μm. However, when carbon nanotubes are used alone as a conductive filler, the surface resistance is excellent (<10 6 Although it is possible to realize a performance of 300 Ohm / sq, there is a deviation in the surface resistance depending on the measurement area. If the carbon nanotube content is increased to solve this problem, the adhesion decreases during the molding process. Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention has been made to solve the above problems, and an object of the present invention is to provide a polyolefin resin foam that can be used to produce a molded product having good adhesion and low surface resistance and surface resistance deviation.

[0009] Another object of the present invention is to provide a molded article produced from the polyolefin resin foam. [Means for solving the problem]

[0010] 1. One embodiment of the present invention provides a polyolefin resin foam comprising: a polyolefin resin; and a conductive filler including carbon nanotubes and carbon black; wherein the weight ratio of the carbon nanotubes to the carbon black is about 1:1.5 to about 1:5.

[0011] 2. In the first embodiment, the foam may include about 87 weight (wt) % or more and about 93 wt % or less of the polyolefin-based resin, and about 7 wt % or more and about 13 wt % or less of the conductive filler.

[0012] 3. In the first or second embodiment, the polyolefin resin may include at least one selected from the group consisting of homo-polypropylene (Homo-PP); a random copolymer in which two or more monomers selected from the group consisting of propylene, ethylene, butylene, and octene are polymerized; a block copolymer in which ethylene-propylene rubber is blended with polypropylene; and a copolymer of polyethylene, ethylene vinyl acetate, and α-olefin.

[0013] 4. In any one of the first to third embodiments, the carbon nanotubes may have an average diameter of about 3 nm to about 15 nm and an average length of about 10 μm to about 25 μm.

[0014] 5. In any one of the first to fourth embodiments, the content of the carbon nanotubes may be about 2 wt % or more and about 3 wt % or less based on the total weight of the foam.

[0015] 6. In any one of the first to fifth embodiments, the carbon black content may be about 5 wt% or more and about 10 wt% or less based on the total weight of the foam.

[0016] 7. In any one of the first to sixth embodiments, the conductive filler may further include one or more selected from the group consisting of graphite, carbon fiber, graphite, graphene, metal powder, metal fiber, and conductive polymer.

[0017] 8. In any one of the first to seventh embodiments, the foam may further include one or more additives selected from the group consisting of antioxidants, UV stabilizers, flame retardants, colorants, plasticizers, heat stabilizers, slip agents, and antistatic agents.

[0018] 9. In the eighth embodiment, the content of the additive may be about 0.1 parts by weight or more and about 15 parts by weight or less based on 100 parts by weight of the total amount of the conductive filler and the polyolefin resin.

[0019] 10. Another embodiment of the present invention provides a molded article produced from the polyolefin resin foam.

[0020] 11. In the tenth embodiment, the surface resistance of the molded article is about 10 1 Ohm / sq or more about 10 6 It may be less than Ohm / sq.

[0021] 12. In the tenth or eleventh embodiment, the surface resistance deviation of the molded article is about 10 0.5 It may be less than Ohm / sq. Effect of the Invention

[0022] The polyolefin resin foam according to one embodiment of the present invention is 6 It is possible to provide a molded product having excellent surface resistance of ohm / sq or less, thereby stably realizing antistatic performance.

[0023] In addition, a molded article manufactured from the polyolefin resin foam according to an embodiment of the present invention exhibits low deviation in surface resistance at different measurement positions, so that a high-quality molded article can be provided.

[0024] The polyolefin resin foam according to one embodiment of the present invention can exhibit good fusion properties during molding. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] In this specification, the singular expression includes the plural expression unless the context clearly indicates otherwise.

[0026] In this specification, the terms "comprise" or "have" mean the presence of features or components described in the specification, but do not preclude the possibility that one or more other features or components may be added.

[0027] As used herein, terms such as "first" and "second" may be used to describe various components, but each component should not be limited by each term. Each term is used only to distinguish one component from another component.

[0028] In interpreting the elements, unless otherwise expressly stated, it is interpreted as including a margin of error.

[0029] In this specification, the terms "a to b" and "a to b" indicating a numerical range are defined as ≧a and ≦b.

[0030] One embodiment of the present invention includes a polyolefin resin; and a conductive filler including carbon nanotubes and carbon black; wherein the weight ratio of the carbon nanotubes to the carbon black is about 1:1.5 to about 1:5 (e.g., 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6). 1:4, 1:4.1, 1:4.2, 1:4.3, 1:4.4, 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9 or 1:5. When the weight ratio of the carbon black to the weight of the carbon nanotubes is less than about 1.5, the polyolefin resin foam is 10. 6 In order to achieve a surface resistance of ohm / sq or less, a high content of carbon nanotubes is necessary. Thus, polyolefin resin foams containing a high content of carbon nanotubes have a problem of poor adhesion between foams during molding, resulting in poor moldability and poor mechanical properties of the final product. In addition, when the carbon black content is less than about 1.5 times the weight of the carbon nanotubes, there is a problem of a significant increase in the deviation of the surface resistance at each measurement position of the molded product. On the other hand, when the weight ratio of the carbon black based on the weight of the carbon nanotubes is more than about 5, problems of dust generation and poor workability due to the excessive amount of carbon black are caused. Specifically, according to one embodiment of the present invention, the weight ratio of the carbon nanotubes to the carbon black may be about 1:1.5 to about 1:4, more specifically about 1:1.5 to about 1:3.5, and even more specifically about 1:1.7 to about 1:3, but is not limited thereto.

[0031] According to one embodiment of the present invention, the polyolefin-based resin foam may include about 87 wt% to about 93 wt% of the polyolefin-based resin (e.g., 87 wt%, 88 wt%, 89 wt%, 90 wt%, 91 wt%, 92 wt% or 93 wt%) and about 7 wt% to about 13 wt% of the conductive filler (e.g., 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt% or 13 wt%). In this case, in the case of a foam containing the polyolefin-based resin and the conductive filler within the above range, it may be more advantageous to produce a molded product having excellent surface resistance and may exhibit better adhesion during molding, but is not limited thereto.

[0032] Hereinafter, the components of the polyolefin resin foam according to one embodiment of the present invention will be described in more detail.

[0033] The polyolefin resin according to one embodiment of the present invention is a base resin for forming a foam, and is light and inexpensive, and can be easily molded by various methods such as injection molding, extrusion molding, and blow molding, and is therefore widely used in automobile materials, packaging materials, building materials, industrial materials, etc. As the polyolefin resin, any polyolefin resin commonly used in the technical field to which the present invention belongs can be used without limitation. Specifically, according to one embodiment of the present invention, the polyolefin resin may include at least one selected from the group consisting of homo-polypropylene (Homo-PP); a random copolymer in which two or more monomers selected from the group consisting of propylene, ethylene, butylene, and octene are polymerized; a block copolymer in which polypropylene is blended with ethylene-propylene rubber; and a copolymer of polyethylene, ethylene vinyl acetate, and α-olefin, but is not limited thereto.

[0034] The carbon nanotube according to one embodiment of the present invention is a material for imparting electrical conductivity to non-conductive polyolefin resins, and refers to a tubular nanomaterial manufactured by rolling a graphite plate, which is made of hexagonal rings of six carbon atoms connected to each other, into a cylinder. When a resin composition containing such carbon nanotubes is foamed and molded, the carbon nanotubes can reduce the surface resistance of the final molded product and improve antistatic performance. The carbon nanotubes may include, without limitation, those known in the art, and specifically, may include at least one selected from the group consisting of single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes, and bundled carbon nanotubes, but are not limited thereto.

[0035] According to one embodiment of the present invention, the carbon nanotubes may have an average diameter of about 3 nm or more and about 15 nm or less (e.g., 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, or 15 nm) and an average length of about 10 μm or more and about 25 μm or less (e.g., 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, or 25 μm), specifically, an average diameter of about 3 nm or more and about 9 nm or less and an average length of about 15 μm or more and about 25 μm or less. Carbon nanotubes having an average diameter and an average length within the above ranges have excellent dispersibility in a polyolefin resin matrix, and have low surface resistance deviation, and may be more advantageous in providing a polyolefin resin foam capable of producing a molded product with further reduced surface resistance, but is not limited thereto. Here, the average diameter of the carbon nanotubes may be measured by an image analysis technique using a TEM, and the average length may be measured by an image analysis technique using a SEM, but is not limited thereto.

[0036] According to one embodiment of the present invention, the content of the carbon nanotubes may be about 2 wt% or more and about 3 wt% or less (e.g., 2 wt%, 2.1 wt%, 2.2 wt%, 2.3 wt%, 2.4 wt%, 2.5 wt%, 2.6 wt%, 2.7 wt%, 2.8 wt%, 2.9 wt%, or 3 wt%) based on the total weight of the foam. In this case, the foam may exhibit better adhesion during molding, and an electrical path may be more easily formed, providing a molded product with lower surface resistance.

[0037] Carbon black according to one embodiment of the present invention is a black fine carbon powder obtained by incomplete combustion of various hydrocarbons or compounds containing carbon. The carbon black is contained in polyolefin resin foam together with carbon nanotubes to impart electrical conductivity and reduce the deviation of surface resistance at each measurement position.

[0038] According to one embodiment of the present invention, the content of the carbon black may be about 5 wt% or more and about 10 wt% or less (e.g., 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, or 10 wt%) based on the total weight of the foam. In this case, the foam may generate less dust and therefore exhibit better workability, which may be more advantageous in providing a molded product with low surface resistance deviation.

[0039] The conductive filler according to an embodiment of the present invention is a component used to improve electrical conductivity and mechanical properties, and may further include a common filler used in the technical field to which the present invention belongs, in addition to the carbon nanotubes and carbon black. Specifically, according to an embodiment of the present invention, the conductive filler may further include at least one selected from the group consisting of graphite, carbon fiber, graphite, graphene, metal powder, metal fiber, and conductive polymer. The size of the conductive filler is not particularly limited, but a conductive filler having an average particle size of about 0.01 μm to about 30 μm may be used.

[0040] In addition, the polyolefin resin foam according to the present invention may further include a conventional additive used in the technical field to which the present invention belongs. Specifically, according to one embodiment of the present invention, the polyolefin resin foam may further include one or more additives selected from the group consisting of an antioxidant, a UV stabilizer, a flame retardant, a colorant, a plasticizer, a heat stabilizer, a slip agent, and an antistatic agent. The additives are added to improve the performance and processing characteristics of the polyolefin resin foam, and various additives known in the art may be used within the scope of the present invention.

[0041] The amount of the additives used may be adjusted to an optimal range within a range known to be usable for producing a polyolefin resin foam, taking into consideration the total production amount and production process, etc. Specifically, according to one embodiment of the present invention, the content of the additives may be about 0.1 parts by weight to about 15 parts by weight based on 100 parts by weight of the total amount of the conductive filler and the polyolefin resin.

[0042] Meanwhile, the polyolefin resin foam may be manufactured by a known method. For example, the method for manufacturing the foam may include the steps of (1) preparing a polyolefin resin composition by mixing a polyolefin resin and a conductive filler including carbon nanotubes and carbon black, (2) introducing the polyolefin resin composition into a reactor, injecting a foaming agent into the reactor, and heating and pressurizing the reactor, and (3) releasing the resin composition in the reactor at a pressure lower than the pressure of the pressurization after the heating and pressurizing step. At this time, the weight ratio of the carbon nanotubes to the carbon black is about 1:1.5 to about 1:5.

[0043] Specifically, in the step (1), the polyolefin resin and the conductive filler are mixed together and then melted and extruded in an extruder to produce a polyolefin resin composition. The melted and extruded polyolefin resin composition may be produced in the form of pellets or beads, specifically in the form of mini-pellets. When the polyolefin resin composition is in the form of mini-pellets, it may be easy to handle during processing. In the process of producing such a resin composition, various functional additives may be mixed with the polyolefin resin and the conductive filler as necessary. The melting and extrusion may be performed under conditions of a screw rotation speed of about 50 rpm to about 500 rpm, an extrusion temperature of about 150° C. to about 240° C., and a residence time of about 5 seconds to about 90 seconds, but is not limited thereto. In addition, a single screw extruder, a twin screw extruder, a kneader, etc. may be used during the melting and extrusion.

[0044] In the step (2), the polyolefin resin composition may be introduced into a reactor in which a dispersion medium containing a dispersant is present, or the dispersant and the dispersion medium may be introduced into the reactor together with the polyolefin resin composition. Then, a foaming agent may be injected into the reactor in which the polyolefin resin composition, the dispersant and the dispersion medium are present, followed by heating and pressurization. At this time, the heating and pressurization may be performed at a temperature of about 130° C. to about 150° C. and about 20 kgf / cm. 2 Approximately 50kgf / cm or more 2 The reaction may be carried out under the following pressure conditions, but is not limited thereto.

[0045] The dispersion medium may include at least one selected from the group consisting of water, ethylene glycol, glycerin, methanol, and ethanol, specifically, but is not limited to, water, and the dispersant may include at least one selected from the group consisting of higher fatty acids, higher fatty acid esters, and higher fatty acid amides, but is not limited to these.

[0046] The foaming agent may be any foaming agent known in the art, and may specifically include at least one selected from the group consisting of propane, butane, hexane, pentane, heptane, cyclobutane, cyclohexane, methyl chloride, ethyl chloride, methylene chloride, dimethyl ether, diethyl ether, methyl ethyl ether, nitrogen, carbon dioxide, and argon. The foaming agent may be added in an amount of about 5 parts by weight to about 50 parts by weight based on 100 parts by weight of the total amount of the polyolefin resin and the conductive filler, and when the amount is within this range, uniform foaming is possible.

[0047] The step (3) may include a step of continuously injecting the foaming agent into the reactor to maintain the pressure. When the resin composition is discharged into the reactor at a low pressure, the foaming agent is continuously injected to prevent the pressure in the reactor from suddenly decreasing, and the contents in the reactor are discharged at a constant pressure, which is preferable for obtaining foamed particles having a uniform appearance and density.

[0048] During the process from step (2) to step (3), i.e., the process of releasing at low pressure, foam cells may be formed in the foam. At this time, the size of the foam cells may be about 30 μm or more and about 400 μm or less. Such a foam may be used to produce a molded product having excellent mechanical properties, and the productivity may be improved.

[0049] Another embodiment of the present invention provides a molded article made from the polyolefin-based resin foam.

[0050] According to one embodiment of the present invention, the surface resistance of the molded article is about 10 1 Ohm / sq or more about 10 6 Ohm / sq or less (e.g., 10 1 Ohm / sq, 10 2 Ohm / sq, 10 3 Ohm / sq, 10 4 Ohm / sq, 10 5 Ohm / sq or 10 6 Ohm / sq), specifically about 10 1Ohm / sq or more about 10 5 It may be less than or equal to about 10 Ohm / sq. 3 Ohm / sq or more about 10 4.5 The polyolefin resin foam according to the present invention can produce a molded product having low surface resistance as described above, and therefore can realize stable antistatic performance.

[0051] According to one embodiment of the present invention, the surface resistance deviation of the molded article is about 10 0.5 It may be less than Ohm / sq. In this way, the difference in surface resistance between measurement points is minimized, thereby providing high quality molded products.

[0052] The molded product can be obtained by a conventional molding method in the technical field to which the present invention belongs, for example, by filling the polyolefin resin foam into a mold, heating it at a high temperature using a heat medium such as steam, and then cooling it.

[0053] The present invention will be described in detail below with reference to examples. However, the following examples are merely for the purpose of illustrating the present invention, and the present invention is not limited to these examples.

[0054] Working Example Example 1 Random polypropylene (manufacturer: Lotte Chemical Co., Ltd., product name: SEP-550, propylene-ethylene random copolymer, Random-PP) 93 wt%, carbon nanotubes (manufacturer: LG Chem, product name: CP1002M, average diameter: 9 nm, average length: 19 μm) 2 wt%, and carbon black (manufacturer: Orion Co., Ltd., product name: HIBLACK (registered trademark) 20L) 5 wt% were fed into a twin-screw extruder (screw diameter 39.8 mm, L / D 40) at a rate of 15 kg / hr, and then melt-extruded under extrusion conditions of a screw rotation speed of 360 rpm and an extrusion temperature of 210°C. The strand-shaped extrudate obtained by the melt-extrusion was cooled with water and then produced into a cylindrical polypropylene resin composition (hereinafter referred to as "polypropylene pellets") weighing 1.0 mg to 1.2 mg and measuring φ0.7 mm x 1 mm using a pelletizer.

[0055] Next, 100 parts by weight of the polypropylene pellets were placed in an autoclave together with 300 parts by weight of water containing 0.5% of a dispersant (manufacturer: Ilshinwells, product name: TWEEN-60, Polyoxyethylene Sorbitan Monostearate). After that, carbon dioxide (CO2) as a foaming agent was placed in the autoclave, and the inside of the autoclave was heated to a temperature of 147°C while stirring, and the pressure was increased to 40 kgf / cm. 2 The contents of the autoclave were then exposed to the air to produce a foam. The expansion ratio was 30 times, and the foam thus produced had foam cells with an average size of 150 μm.

[0056] The foam was then dried in an oven at 60° C. for 24 hours. The dried foam was stored at room temperature and atmospheric pressure for 48 hours, and then filled into a mold (450 mm×450 mm×50 mm). Saturated steam (pressure: 2.5 bar) was then supplied to the mold for 30 seconds to fuse the foam together and mold it, and the molded product was then dried in an oven at 60° C. for 24 hours.

[0057] Examples 2 to 3 and Comparative Examples 1 to 4 A molded article was manufactured in the same manner as in Example 1, except that the amounts of the Random-PP, carbon nanotubes, and carbon black were adjusted as shown in Table 1 below.

[0058] Example 4 A molded product was manufactured in the same manner as in Example 1, except that carbon nanotubes having an average diameter of 10 nm and an average length of 14 μm (manufacturer: LG Chem, product name: LUCAN BT1003M) were used instead of the carbon nanotubes used in Example 1.

[0059] <Evaluation method> 1. Average surface resistance (unit: Ohm / sq) The surface resistance of each of the molded articles manufactured in Examples 1 to 4 and Comparative Examples 1 to 4 was measured in five different regions (specifically, the front, rear, both sides, and center) using a surface resistance tester (SIMCO, ST-4), and the average surface resistance was calculated.

[0060] 2. Surface resistance deviation (unit: Ohm / sq) The surface resistance of each of the molded products manufactured in Examples 1 to 4 and Comparative Examples 1 to 4 was measured in five different regions (specifically, the front, back, both sides, and center) using a surface resistance tester (SIMCO, ST-4), and the average surface resistance was calculated, and the difference in surface resistance in each region from the average surface resistance was measured. At this time, the smaller the deviation in surface resistance, the more uniform the surface resistance is in each region.

[0061] 3.Fusion (moldability) The molded articles produced in Examples 1 to 4 and Comparative Examples 1 to 4 were folded and crushed, and the cross sections were photographed under a microscope to evaluate the fusion properties of each foam based on the observed shape. Specifically, when the foam was observed to be split or cracked on the crushed surface of the molded article, the fusion properties were judged to be good, and when the foam surface was observed to be exposed on the crushed surface, the fusion properties were judged to be poor.

[0062] [Table 1]

[0063] Referring to Table 1, in the case of the molded products manufactured according to Examples 1 to 4 containing carbon nanotubes and carbon black in a ratio of about 1:1.5 to about 1:5, the molded products had a 10 6 Low surface resistance of less than 10 Ohm / sq and 0.5 It can be seen that the foams produced in Examples 1 to 4 all exhibited good adhesion, and that the surface resistance deviation was low, less than Ohm / sq.

[0064] On the other hand, the molded products manufactured according to Comparative Examples 1, 2, and 4, in which the carbon black content based on carbon nanotube 1 is less than about 1.5, showed poor fusion properties. And, the molded product manufactured according to Comparative Example 3, in which the carbon black content based on carbon nanotube 1 is more than about 5, showed higher surface resistance and slightly lower fusion properties than the molded products manufactured according to Examples 1 to 4.

[0065] Meanwhile, the molded products of Examples 1 to 3, which contain carbon nanotubes with an average diameter of 9 nm and an average length of 19 μm, exhibit lower surface resistance than the molded product of Example 4, which contains carbon nanotubes with an average diameter of 10 nm and an average length of 14 μm. This confirms that the antistatic performance of the foam can be further improved by adjusting the average diameter and average length of the carbon nanotubes.

[0066] The present invention has been described above with reference to the embodiments. Those skilled in the art will understand that the present invention can be embodied in modified forms without departing from its essential characteristics. Therefore, the disclosed embodiments should be considered from an explanatory perspective, not a limiting one. The scope of the present invention is defined in the claims, not the above description, and all differences within the scope of the equivalents should be interpreted as being included in the present invention.

Claims

1. Polyolefin resin; and a conductive filler comprising carbon nanotubes and carbon black; The content of the carbon nanotubes is 2 wt % or more and 3 wt % or less based on the total weight of the foam, The polyolefin resin foam, wherein the weight ratio of the carbon nanotubes to the carbon black is 1:1.5 to 1:

5.

2. 2. The polyolefin resin foam according to claim 1, wherein the foam contains 87 wt % or more and 93 wt % or less of the polyolefin resin and 7 wt % or more and 13 wt % or less of the conductive filler.

3. The polyolefin-based resin foam according to claim 1 or 2, characterized in that the polyolefin-based resin comprises at least one selected from the group consisting of homo-polypropylene (Homo-PP); a random copolymer in which two or more monomers selected from the group consisting of propylene, ethylene, butylene, and octene are polymerized; a block copolymer in which ethylene-propylene rubber is blended with polypropylene; and a copolymer of polyethylene, ethylene vinyl acetate, and α-olefin.

4. 4. The polyolefin resin foam according to claim 1, wherein the carbon nanotubes have an average diameter of 3 nm or more and 15 nm or less, and an average length of 10 μm or more and 25 μm or less.

5. The polyolefin resin foam according to claim 1 , wherein the carbon black content is from 5 wt % to 10 wt % based on the total weight of the foam.

6. 6. The polyolefin resin foam according to claim 1, wherein the conductive filler further comprises at least one selected from the group consisting of graphite, carbon fiber, graphite, graphene, metal powder, metal fiber, and conductive polymer.

7. The polyolefin resin foam according to any one of claims 1 to 6, further comprising one or more additives selected from the group consisting of antioxidants, UV stabilizers, flame retardants, colorants, plasticizers, heat stabilizers, slip agents, and antistatic agents.

8. The polyolefin resin foam according to claim 7, wherein the content of the additive is from 0.1 parts by weight to 15 parts by weight based on 100 parts by weight of the total amount of the conductive filler and the polyolefin resin.

9. A molded article produced from the polyolefin resin foam according to any one of claims 1 to 8.

10. The surface resistance of the molded product is 10 1 Ohm / sq or more 10 6 The molded article according to claim 9, characterized in that it has a hardness of ohm / sq or less.

11. The surface resistance deviation of the molded product is 10 0.5 The molded article according to claim 9 or 10, characterized in that it has a compressive strength of Ohm / sq or less.

Citation Information

Patent Citations

  • Composite carbon material with increased miscibility and continuous production method and device thereof

    JP2012532085A

  • Electrically conductive interconnecting porous film and production method thereof

    JP2013139550A

  • Highly conductive foam composition having carbon composite

    KR1020100136079A

  • Resin sheet and adhesive-layer-having resin sheet

    WO2019044422A1